Evaluating the Effectiveness of the Cerdas App and its Interventions in Addressing Mental Health Issues (Depression, Anxiety, and Stress) Among Adolescents - Nenty Septiana; Suci Zahratul Liza; Nurul Kamaly (Universitas STRADA Indonesia, 2025)
Background: Adolescent mental health issues are on the rise, posing significant concerns due to their impact on learning effectiveness and the need for focused attention. To address these challenges, innovative tools are required to detect and mitigate mental health problems among adolescents. One such innovation is the CERDAS application. Purpose: This study evaluated a web-based assessment using the CERDAS App, which combines three interventions: mental health education, the butterfly hug technique, and expressive writing in addressing depression, anxiety, and stress among adolescents. Methods: This research employed a Research and Development (R&D) approach with a quasi-experimental design, specifically a one-group pretest-posttest method. A total of 94 adolescents were selected through purposive sampling from a high school in Banda Aceh, Indonesia. The Depression Anxiety Stress Scales (DASS)-21, Indonesian version, was used as the questionnaire within the CERDAS application. Data collection began with a pretest administered via the CERDAS App. Adolescents identified as experiencing mental health problems (depression, anxiety, or stress) were provided with interventions including mental health education, butterfly hugs, and expressive writing. Data were analyzed using univariate analysis for frequency distribution and bivariate analysis with the Wilcoxon test. Results: The Wilcoxon test revealed significant improvements in the mental health status of adolescents (depression, anxiety, and stress) following the interventions, with p-values of 0.002, 0.008, and 0.001, respectively. Conclusion: The CERDAS application and its interventions demonstrate effectiveness in identifying and reducing adolescent mental health problems, including depression, anxiety, and stress. Consequently, the CERDAS App and its interventions is recommended as a practical tool for adolescents to enhance their mental well-being.